Fruit By-Product Processing and Bioactive Compounds - Mohammed Saleh; Lana Amro; Haya Barakat; Rahma Baker; Amani Abu Reyash; Reham Amro; Jihad Qasem (Journal of Food Quality)
Total phenolic content (TPC), total flavonoid content (TFC), ferric reducing antioxidant potential (FRAP), and diphenyl-1-picrylhydrazyl (DPPH) free radical scavenging activity of avocado peel, avocado seeds, kiwi fruit, orange peel, pineapple peel, and pomegranate skin by-products during processing (i.e., dried, blanched, freezed, and fresh) were determined. It was hypothesized that fruit by-products would add a significant value to the food products. Heat treatments resulted in increasing TPC and TFC and reducing power of fruit by-products with avocado peels TFC of 136.9 and 63.1 mg/100 g of dried and blanched treatments, respectively, compared to 14.4 mg/100 g of fresh and 20.6 mg/100 g of freezed treatments. Orange peels TFC increased from 54.4 mg/100 g of fresh to 194.4 and 380.0 mg/100 g for blanched and dried treatments, respectively. Fresh treatments had the lowest DPPH (%) (IC50), indicating a significant effect of blanching and drying on fruit by-product antioxidant activity with some exceptions. IC50 increased from 20.0 of fresh to 39.8% of dried pineapple peel and from 6.5 to 15.0% for pomegranate skin of fresh and dried treatments, respectively. The use of fruit by-products regardless to its processing as supplements to flours would significantly increase flour’s bioactive availability.